Problems of immunologic diagnostics of celiac disease among children - Ye. A. Roslavtseva; Yu. А. Lysikov; Т. Ye. Lavrova; Т. E. Borovik (Бюллетень сибирской медицины, 2005)
In the review it is observed the importance of determination of serum antibodies of different classes (IgA, IgG) to gliadine, reticulin, endomysium, tissue transglutaminase for diagnostics and screening under celiac disease, advantages and disadvantages of methods, peculiarities of immunologic reactions under celiac disease among children of different age, dynamics of titres of antibodies on the background of observance and non observance of gluten-free diet, place of immunologic methods in complex diagnostic of celiac disease and for control for diet observance.